2011
DOI: 10.1111/j.1346-8138.2010.01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in methylprednisolone pulse therapy for alopecia areata

Abstract: Many treatments induce remission in patients with alopecia areata. Systemic steroids, for example, are effective in the treatment of severe alopecia areata but have many side-effects. To avoid these side-effects, high-dose bolus infusions of methylprednisolone have been used to treat severe alopecia areata. The purpose of this study was to evaluate the prognostic factors associated with pulse therapy and to establish proper indications for methylprednisolone pulse therapy. Seventy patients with severe alopecia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
46
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(57 citation statements)
references
References 14 publications
8
46
3
Order By: Relevance
“…In the group described in the present study, only 3 patients had adverse effects of treatment, all of which were mild, and none required cessation of treatment. Previous studies reported similar findings [4,8,9,15,16,17,19,20,21,22]. …”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…In the group described in the present study, only 3 patients had adverse effects of treatment, all of which were mild, and none required cessation of treatment. Previous studies reported similar findings [4,8,9,15,16,17,19,20,21,22]. …”
Section: Discussionsupporting
confidence: 74%
“…Be that as it may, it is likely that outcome was affected by the presence of certain factors. Short disease duration (≤6 months) was a positive prognostic factor in our study and was also associated with favorable results in previous studies in both adults [19] and children older than 12 years [20]. The better response associated with early disease may be explained by findings of fewer functional follicular structures and some follicular scarring in patients with long-standing AA [23].…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations